In-line determination of adsorbed fatty acids on magnesium silicate with conductivity measurement - (:unkn) unknown (My University, 2012)
The sorption of two fatty acids namely lauric and myristic acid onto synthetic magnesium silicate produced from rice hull ash silica has been studied. Conductivimeter was used for in-line determination of adsorption process. The sorption characteristics of magnesium silicate were determined by both chemical and FT-IR analysis. Kinetic studies showed that adsorption of lauric and myristic acid onto synthetic magnesium silicate followed pseudo-secondorder kinetics. Adsorption equilibrium isotherms for lauric and myristic acids were analyzed by Freundlich and Langmuir isotherm models. Langmuir isotherm model was found to best represent the data for Lauric and myristic acid onto synthetic magnesium silicate. Isotherms have also been used to obtain the free energy, enthalpy and entropy of the adsorption. The thermodynamic results indicated that the adsorption process was an endothermic, which occurred spontaneously. © by PSP.
Keywords: Adsorption isotherms; Adsorption kinetics; Fatty acids; Rice hull ash